How the online environment can facilitate or hinder Creative Problem Solving process among international students, and how this environment help the recognition of a creative person in international business environment? - Ivanov, Ilia (2014)
This qualitative study investigates how different factors such as cultural and educational backgrounds, timeframes, mood factor, team-bonding, team trust, levels of language and engagement, as well as task and relationship conflicts affect creative problem solving (CPS) processes in two opposing environments: ‘online’ and ‘offline’. Ten respondents from seven different countries were gathered, in order to provide multicultural diversity, for the purpose of this study. They were divided into two groups chosen at random to go through a CPS ‘online’ process. After that, ten semi-structured interviews were conducted with each participant and analyzed. In addition, one more factor was added to the interview protocol: personal estimation of the creative individual, to establish views on how an individual assesses him or herself in a creative group collaboration. Finally, interesting correlations were found between the different factors and two environments. They were discussed, in order to provide a deeper insight for further research and organizational implementations.